2019
DOI: 10.1002/aenm.201803210
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin 2D TiS2 Nanosheets for High Capacity and Long‐Life Sodium Ion Batteries

Abstract: greenhouse emissions and environmental pollution can be effectively reduced. In this regard, sodium ion batteries (SIBs) possess the merits of low cost and abundance. [1,2] The sluggish kinetics of sodium ion diffusion caused by the large sodium ionic radius, however, results in poor cycling stability, and low rate performance. Fully understanding the structural evolution during electrochemical reactions and achieving the corresponding improvements in the crystal structure and morphology design are urgently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 41 publications
3
79
0
Order By: Relevance
“…The few-layer MoS 2 nanosheets were in situ grown on the surface of rGO as well as HCS by hydrothermal method. [38] As shown in Figure 3c, the TEM image clearly identified the 3D interconnected [94] structure, where the MoS 2 nanosheets well cross-linked with hollow nanospheres and the rGO surface. Also, the HRTEM images revealed that the number of layers of MoS 2 can be tuned from single-layer to few-layer (2-5 layers) with an enlarged interlayer distance of 0.69 nm (vs. 0.62 nm for pristine MoS 2 ) (Figure 3d).…”
Section: Hydrothermal/solvothermalmentioning
confidence: 84%
See 1 more Smart Citation
“…The few-layer MoS 2 nanosheets were in situ grown on the surface of rGO as well as HCS by hydrothermal method. [38] As shown in Figure 3c, the TEM image clearly identified the 3D interconnected [94] structure, where the MoS 2 nanosheets well cross-linked with hollow nanospheres and the rGO surface. Also, the HRTEM images revealed that the number of layers of MoS 2 can be tuned from single-layer to few-layer (2-5 layers) with an enlarged interlayer distance of 0.69 nm (vs. 0.62 nm for pristine MoS 2 ) (Figure 3d).…”
Section: Hydrothermal/solvothermalmentioning
confidence: 84%
“…MSs (MS x , M=Fe, Co, Ni, Cu, Zn, Sb, Bi, Ti) have a low price raw‐material source and high theoretical capacity, which make them very competitive compared to other anode materials . Also, the layered metal sulfides (MS x , M=Mo, Sn, W, V), have a similar layered structure of graphite, showing an excellent cycling performance .…”
Section: Introductionmentioning
confidence: 99%
“…[72] Hu et al synthesized ultrathin TiS 2 nanosheets by as hear-mixingm ethod, which exhibited outstanding cycling performance in SIBs with 386 mAh g À1 after 200 cycles at 0.2 Ag À1 . [73] Sun et al prepared MoS 2 /graphene nanosheets by ball milling and exfoliation of commercialb ulky MoS 2 and graphite. [74] As anode materials for SIBs, the as-prepared MoS 2 / graphene nanosheets exhibited remarkably high rate capability with capacities of 284 mAh g À1 at 20 Ag À1 and 201 mAh g À1 at 50 Ag À1 .C ompared with TMDs, MXenes usually have much higher conductivities and larger tunable interlayer spacings, which maket hem promising host materials for Na.…”
Section: Alkali Metal-ion Batteriesmentioning
confidence: 99%
“…[9,10] Compared to Li-ion batteries, sodium-ion batteries (SIBs) have aroused growing research interests in large-scale energy storage systems because of low prices and rich natural abundance of sodium. [11,12] In addition, SIBs have similar chemistry intercalation mechanism with LIBs, which are based on the reversible Na ions intercalation/deintercalation in the positive and negative electrodes during discharge and charge process. [13,14] Generally, favorable anode materials with long life, great cycling stability and high rate performance, are the most important factors for the commercial development of SIBs.…”
Section: Introductionmentioning
confidence: 99%